THE REFLECTION OF HEROISM IN THE SHORT STORIES OF E. HEMINGWAY. - Odilova Farangiz (TADQIQOTLAR.UZ, 2024)
ABSRACT This article examines the theme of heroism in the short stories of Ernest Hemingway, delving into the ways in which his characters grapple with notions of bravery, sacrifice, and moral integrity within the constraints of shorter narrative forms. Through a close analysis of select short stories such as "The Snows of Kilimanjaro," "The Short Happy Life of Francis Macomber," and "A Clean, Well-Lighted Place," this study seeks to uncover the nuances and complexities of heroism as depicted by Hemingway. By considering the impact of war, masculinity, and existentialism on his characters' actions and decisions, this article aims to provide insight into Hemingway's exploration of heroism in the context of the modern world. Through his economical prose and vivid characterizations, Hemingway invites readers to question conventional notions of heroism and confront the moral ambiguities inherent in human experience.